FOMO and Digital Loans Drive Impulsive Purchases Among Gen Z - Nurul Hidayah; Aqwa Naser Daulay; Kusmilawaty Kusmilawaty (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The surge of digital consumption among Generation Z has redefined consumer behavior, particularly through platforms like TikTok Shop. Specific Background: In Indonesia, this generation actively engages in social commerce, driven by psychological and financial enablers. Knowledge Gap: While previous studies have explored hedonism, FOMO, and online loans separately, few have assessed their combined effects on impulsive buying in a specific metropolitan context. Aims: This study investigates the collective and individual roles of hedonism, FOMO, and online loans in driving impulsive buying among Gen Z in Medan City. Results: Using a quantitative survey with 100 respondents and multiple linear regression analysis, the findings indicate that FOMO and online loans significantly predict impulsive buying behavior, while hedonism does not show a significant effect. The combined model accounts for 50.3% of the variance in impulsive purchasing. Novelty: This study offers a localized empirical perspective integrating psychological and financial dimensions in a digital context, while introducing Islamic banking as a potential moderating discourse. Implications: The findings suggest a need for financial literacy programs and responsible lending policies targeting youth, while offering marketers insights into Gen Z’s primary consumption triggers. Highlights: FOMO and online loans are key drivers of impulsive buying in Gen Z Medan. Hedonism has no significant predictive value for impulsive buying in this context. Combined predictors explain over 50% of impulsive buying behavior variance. Keywords: Gen Z, impulsive buying, FOMO, online loans, hedonism